Komunikasi Persuasif Rumah Masker dalam Mengembalikan Brand Awareness - Safitri, Novi; Asniar, Immawati; Choiriyati, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Social media, particularly Instagram, has become an essential platform for local brands to build interaction and strengthen brand awareness. However, a period of digital inactivity presents significant challenges in maintaining audience relationships. This study aims to describe the persuasive communication strategies implemented by Rumah Masker in restoring brand awareness after being inactive on Instagram. The research employed a qualitative approach through in-depth interviews, content observation, and documentation. The findings reveal that Rumah Masker’s persuasive communication strategies were carried out through consistent visual content and storytelling, active interaction with audiences, collaborations with influencers, and structured content planning. These strategies proved effective in increasing engagement, enhancing message credibility, and rebuilding consumer trust. The study concludes that persuasive communication serves not only as a promotional tool but also as a recovery strategy to maintain brand existence in the competitive local beauty market.